2015
DOI: 10.5688/ajpe798119
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Pharmacy Students in Qatar on Anti-Doping in Sports and on Sports Pharmacy in Undergraduate Curricula

Abstract: Objective. To assess pharmacy students' knowledge and perceptions of doping and anti-doping in sports and to explore the curricular needs for undergraduate pharmacy in the field of sports pharmacy. Methods. A cross-sectional, descriptive, web-based survey of pharmacy students was conducted at Qatar University College of Pharmacy from March to May 2014. Data were analyzed using descriptive and inferential statistics. Results. Eighty respondents completed the online survey (80% response rate). Sixty percent were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
5
27
1
1
Order By: Relevance
“…A continuing professional development module could also be designed for training practicing pharmacists to play a more effective role in sports events and/or work in association with hospitals or clinics that primarily focus on sports patients. [8] In alignment with previous studies [6,7,8] , this study indicated that pharmacy students support sports pharmacy being incorporated into the curriculum. Many of the findings were in line with previous studies [5][6][7][8].…”
Section: Figure 1: Respondents' Knowledge On the Presence Of Prohibitsupporting
confidence: 80%
“…A continuing professional development module could also be designed for training practicing pharmacists to play a more effective role in sports events and/or work in association with hospitals or clinics that primarily focus on sports patients. [8] In alignment with previous studies [6,7,8] , this study indicated that pharmacy students support sports pharmacy being incorporated into the curriculum. Many of the findings were in line with previous studies [5][6][7][8].…”
Section: Figure 1: Respondents' Knowledge On the Presence Of Prohibitsupporting
confidence: 80%
“…The questionnaire used in the present study was adapted from previous literature in the area . The survey comprised four sections (A–D).…”
Section: Methodsmentioning
confidence: 99%
“…Section A collected information about the sociodemographic background of the students and Section B evaluated their knowledge of doping. Section B tested the ability of the respondents to recognise, from a list of eight substances, those substances that are prohibited under WADA's annually renewed Prohibited List . Knowledge was assessed on the basis of the marks the respondents obtained in this section, with each correct answer awarded 1 mark, whereas wrong answers or answering ‘Don't know’ were given a mark of 0.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the survey questions were adopted from previously validated surveys and tailored to meet the objectives of the current study (20)(21)(22). Previous questionnaire-based studies in Qatar have shown that surveys in English can be an effective tool to gather information from practising pharmacists in Qatar, even though the majority of pharmacists originate from Arabic-speaking countries (20,23).…”
Section: Questionnairementioning
confidence: 99%